Model pembelajaran teams games tournament (tgt) dalam perspektif pendekatan aktif pendidikan: analisis literatur - Rahmawati, Ainia Fikri (Maliki Interdisciplinary Journal, 2025)
As one of the active learning innovations, teams games tournament (TGT) is considered to improve class dynamics, social interaction, and concept understanding at various levels of education and various subjects. This study aims to explore the application, advantages, challenges, and effectiveness of TGT in improving student motivation and learning outcomes through literature analysis. This research is a qualitative research with data collection through library research and then analyzed using Miles and Huberman’s interactive analysis technique. The teams games tournament (TGT) learning model is an innovative approach that integrates elements of competition and teamwork, making it effective in improving motivation, student engagement and learning outcomes. In addition, TGT supports active learning by developing social skills such as responsibility, communication and cooperation among team members. Despite challenges in its implementation, such as ability gaps between students and relatively long time requirements, TGT remains relevant for various levels of education and subject areas. With careful planning and adequate support, this model can create a learning atmosphere that is fun, interactive, and supports the development of 21st century skills.